Evaluation Of The Tuberculosis Surveillance System In The Municipality Of Uruguaiana/RS, In The Years 2019 And 2020 - Sarmento, Silvia Muller de Moura; Pinto, Rodrigo Silveira (Seven Editora, 2023)
The Sistema de Informação de Agravos de Notificação (SINAN) was developed with the objective of collecting, transmitting and disseminating data routinely generated by the Epidemiological Surveillance System (SVE), especially for compulsorily notifiable diseases, including tuberculosis (TB). TB is a health emergency, according to the WHO, in Brazil it is considered a public health problem, and the municipality of Uruguaiana is a priority for combating TB in the state of Rio Grande do Sul (RS). Objective: to evaluate the Tuberculosis Surveillance System (SVT) in relation to data quality and representativeness of the information system, in Uruguaiana/RS, in the period 2019-2020. Methodology: A cross-sectional descriptive study was conducted to evaluate the data quality (consistency) and representativeness of the non-nominal SINAN database, with the aid of EpiInfo7™ software. Results: 76 notifications were found in the year 2019 and 74 in the year 2020, which pointed to an excellent completeness of the mandatory items of SINAN, and regular completeness of the essential items. Regarding representativeness, it showed that it has a greater male coverage, with age ± 41 years. Regarding the complementary data, it showed the predominance of pulmonary TB and its relations with HIV co-infection, population deprived of freedom and smokers, individuals susceptible to infections by the bacillus. Conclusion: The monitoring of the attributes should be continuous, and the results may assist in the decision-making of health surveillance and managers. DOI: https://doi.org/10.56238/colleinternhealthscienv1-109